Phytochemical Analysis and Antiurolithiatic Activity of Aqueous Fruit Extract of Momordica charantia Linn in Ethylene Glycol-induced Urolithiasis Rats Model - Vishwakarma, Ms. Harshna (International Journal of Pharmaceutical & Biological Archive, 2022)
In the indigenous system of medicine, the fruits of Momordica charantia Linn. (Family- Cucurbitaceae) are reported to be useful in the treatment of urinary stones. However, enough scientific evidences were not available about the effect of this plant as nephroprotective and antiurolithic. Hence, the aim of the present study was to evaluate qualitative phytochemical analysis and antiurolithiatic activity of an aqueous extract from the fruits of M. charantia collected from Sagar region of Madhya Pradesh. Qualitative analysis of various phytochemical constituents was determined by the well-known test protocol available in the literature. Ethylene glycol (0.75%) in drinking water was fed to all the groups (Groups II-V) except normal control (Group I) for 28 days to induce urolithiasis for curative and preventive regimen. Groups I, II, and III served as normal control, negative control (hyperurolithiatic), and standard (Allopurinol 120 mg/kg), Groups IV and V were treated with aqueous extracts of M. charantia fruits (100 mg/kg and 200 mg/kg), respectively. The urolithiasis-related biochemical parameters were evaluated in the rat’s urine and serum. Phytochemical analysis revealed the presence of carbohydrates, alkaloids, saponins, and flavonoids. The treatment with aqueous extract (100, 200 mg/kg, p.o) of fruits of M. charantia significantly lowered (P < 0.001) the increased levels of serum creatinine, urine protein, and urine calcium. The treatment with aqueous extract fruits significantly (P < 0.001) increases levels of urine output, urine creatinine, and serum calcium. The results were comparable to that of negative control group. The presented data indicate that administration of M. charantia fruits extracts to rats with experimentally-induced urolithiasis reduced and also prevented the formation of urinary stones, supporting folk information regarding antiurolithiatic activity of the plant. The reduction in the stone forming constituents in urine and renal tissue brought about by M. charantia could contribute to its antiurolithiatic property